Rethinking Giftedness and Talent in Sport - Tranckle, P.; Cushion, C. J. (Quest, 2006)
The purpose of this paper is to understand how gifts are discovered and talents developed within sport. The current literature is critically discussed, highlighting contributions and gaps in current knowledge. Due to issues concerning terminology and the nature versus nurture debate, research on talent faces challenges relating to continuity and meaningful progression. Williams and Reilly`s (2000) definitions, along with Gagné`s Differentiated Model of Giftedness and Talent are introduced and used to organize and add conceptual clarity to the existing knowledge base. Using Gagné`s model, areas for further research begin to evolve. A case is made for the qualitative exploration of how gifts are discovered and why people commit to talent development, noting the advantages of phenomenological methods.